Effect of hay supplementation timing on rumen microbiota in suckling calves. Issue 1 (27th December 2017) - Lin, Xueyan; Wang, jian; Hou, Qiuling; Wang, Yun; Hu, Zhiyong; Shi, Kerong; Yan, Zhengui; Wang, Zhonghua
Abstract: An animal feeding trial was conducted on 18 seven‐day‐old Holstein dairy bull calves weighing 42 ± 3 kg each. Calves were randomly assigned into three groups ( n  = 6 each). The dietary treatments were as follows: (1) milk and starter for the control group (MS), (2) supplementation of oat hay from week 2 on the basis of milk and starter (MSO2), and (3) supplementation of oat hay from week 6 on the basis of milk and starter (MSO6). All animals were fed starter and oat hay ad libitum. The major phyla in the different groups of rumen fluid included Firmicutes, Actinobacteria, Bacteroidetes, Proteobacteria, and Euryarchaeota. The major genera were identified, and major genera proportions in the three groups were as follows: Methanobrevibacter (Euryarchaeota), 2.1%, 1.7%, and 2.1%; Olsenella (Actinobacteria), 23.9%, 17.7%, and 12.8%; Prevotella (Bacteroidetes), 10.5%, 16.5%, and 19.2%; Dialister (Firmicutes), 3.3%, 4.1%, and 2.8%; Succiniclasticum (Firmicutes), 3.8%, 4.7%, and 9.2%; and Sharpea (Firmicutes), 0.4%, 2.5%, and 0.2%, respectively. There were no significant differences in the various phyla among the three groups ( p  > .05). The results showed that calves hay supplementation time did not affect the diversity of the rumen microbiota in the suckling calves. However, the hay supplementation altered the proportion of the various microbial populations, supplementation of oat hay from week 2 on the basis of milk and starter could improve calves rumen pH. Abstract : Hay supplementation did not affect the diversity of the rumen microbiota in the suckling calves. However, the hay supplementation altered the proportion of the various microbial populations, and their structural differences indirectly affected the rumen pH.